2021
DOI: 10.1002/jmv.27442
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with mechanical ventilation in SARS‐CoV‐2 patients treated with high‐flow nasal cannula oxygen and outcomes

Abstract: Five percent of patients infected with SARS-CoV-2 require advanced respiratory support. The high-flow nasal cannula oxygenotherapy (HFNCO) appears to be effective and safe to reduce the need for mechanical ventilation. However, the factors associated with HFNCO failure as well as the outcomes of patients receiving this noninvasive respiratory strategy remain unclear. Thus, we performed this study to determine factors leading to intubation of SARS-CoV-2 patients treated with HFNCO and patients' outcomes. We ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Other therapy management was performed according to valid recommendations 25–29 . Consistent with some other studies, patients requiring high‐flow oxygen deteriorated to requiring ventilatory support usually within 24–48 h 30–32 …”
Section: Resultsmentioning
confidence: 87%
“…Other therapy management was performed according to valid recommendations 25–29 . Consistent with some other studies, patients requiring high‐flow oxygen deteriorated to requiring ventilatory support usually within 24–48 h 30–32 …”
Section: Resultsmentioning
confidence: 87%
“…Leroux et al reported in their study that in 47.8% of cases, HFNO prevented the need for intubation [2]. Additional studies have found that HFNO may enhance the prognosis and decrease mortality [2,12].…”
Section: Introductionmentioning
confidence: 95%
“…The World Health Organization (WHO) advised regular monitoring of oxygenation in severe patients to determine the need for oxygen therapy [1]. About fourteen percent of individuals develop hypoxemic respiratory failure and require oxygen therapy, while five percent require even more intensive breathing assistance [2]. The spread of the virus exceeded hospitals' capacity for moderate and severe patients by mid-2020, resulting in a global shortage of mechanical ventilators.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation